Repair Performance Landslide and Slope Using Bore pile and Ground Anchor on Cipali Toll Road Km 103 - Akhmudiyanto Akhmudiyanto; Paulus Pramono Rahardjo; Rinda Karlinasari (Kadiri University, 2021)
One of the causes of on-road collapse slopes is traffic load. Slope failure by road loads usually occurs due to several factors such as soil type, rainfall, land use. This study aims to determine landslide and slope repair performance using bore pile and ground anchor on Cipali Toll Road KM 103. The research method used in this study is the Finite element method. In this research, data collection, modeling parameter determination, slope stability analysis, slope reinforcement analysis, and reinforcement design were carried out with variations in bore pile and ground anchor dimensions. The software program used is a finite element program in the form of PLAXIS to analyze slope stability and estimate the slope failure area. The result of the study is that the R-Value inter is 0.25 with a 1.0341 safety factor. Best repair performance obtained from the addition of reinforcement with ground anchor 2 layer on bore pile 2 with a distance of 2 meters increased the safety factor to 1,913; Borepile capacity calculation with the calculation of normal force and moment iteration, the largest occurs in the DPT (Retaining Wall) stage with a normal load of -37.9 and a moment force of -471.15 which is still able to be borne by bore pile 1. The result of this study is expected to be benchmark and repair material to improve slope stability at km 103 Tol Cipali